Nursing Perception of the Impact of Medication Carts on Patient Safety and Ergonomics in a Teaching Health Care Center. (April 2013) - Rochais, Élise; Atkinson, Suzanne; Bussières, Jean-François
Objectives: In our Quebec (Canada) University Hospital Center, 68 medication carts have been implemented as part of a nationally funded project on drug distribution technologies. There are limited data published about the impact of medication carts in point-of-care units. Our main objective was to assess nursing staff's perception and satisfaction of medication carts on patient safety and ergonomics. Method: Quantitative and qualitative cross-sectional study. Data were gathered from a printed questionnaire administered to nurses and an organized focus group composed of nurses and pharmacists. Results: A total of 195 nurses completed the questionnaire. Eighty percent of the nurses agreed that medication carts made health care staff's work easier and 64% agreed that it helped to reduce medication incidents/accidents. Only 27% and 43% agreed that carts' location reduces the risk of patients' interruptions and colleagues' interruptions, respectively. A total of 17 suggestions were extracted from the focus group (n = 7 nurses; n = 3 pharmacist) and will be implemented in the next year. Conclusions: This descriptive study confirms the positive perception and satisfaction of nurses exposed to medication carts. However, interruptions are a major concern and source of dissatisfaction. The focus group has revealed many issues which will be improved.